Two new species of Metacyclops Kiefer, 1927 (Copepoda, Cyclopoida) from Thailand and an up-to-date key to the species recorded in Asia - Athibai, Sujeephon; Wongkamhaeng, Koraon; Boonyanusith, Chaichat (European Journal of Taxonomy, 2022)
Metacyclops sakaeratensis sp. nov. and M. brancelji sp. nov. are described as being present in the mountainous areas of Northeastern and Southern Thailand, respectively. Two new species resemble M. woni in both sexes, but they are easily distinguished from their Cambodian relative by having: 1) transverse suture on the dorsal surface of the genital double-somite, 2) serrated hyaline frill on the posterior margin of third pedigerous somite, 3) different length / width ratio of caudal ramus, and 4) a row of spinule on caudal surface of intercoxal sclerite of the third swimming legs. The significant differences between M. sakaeratensis sp. nov. and M. brancelji sp. nov. are present in both sexes, including the body size, integumental ornamentation of the body surface, length / width ratio of caudal ramus, armature of the fifth swimming leg, and the male sixth swimming leg. In addition, an up-to-date key to the female of all fifteen species of Metacyclops recorded in Asia is provided.